KINERJA GURU DITINJAU DARI PENGARUH BUDAYA ORGANISASI DAN GAYA KEPEMIMPINAN KEPALA SEKOLAH - Handayani, Esti; Lian, Bukman; Rohana, Rohana (Graduate Program Magister Manajemen Pendidikan, 2021)
This study determined the effect of organizational culture and leadership style in school principals on improving teacher’s performance in Muara Padang. This research used quantitative methods with correlational type. The study population was 60 people. The research sample was 51 people, where the sampling technique using a method developed by Isaac and Michael with an error rate of 5%. The results showed: 1) there was a positive and significant influence of organizational culture on teacher’s performance; 2) there is a positive and significant influence between the principal's leadership style and the teacher's performance; 3) there is a simultaneous influence between organizational culture and school principal leadership style on teacher’s performance in Muara Padang.